1998
DOI: 10.1023/a:1011979505697
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The IPC solutions exhibit phase transformation in vivo. and demonstrate no evidence of toxicity. The pharmacological effects observed from the of release of 3A2-ATG-psODNs suggest that the formulation can entrap, protect, and sustain the delivery of macromolecules. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Aqueous solutions of P407 above a concentrations of about 20% (w/w) are liquid when refrigerated, but gel upon warming 11. However, application of concentrated polymer solutions (>16%) in drug delivery may be disadvantageous as it changes the osmolality of the formulation, kinetics of gelation, and causes discomfort in ophthalmic applications due to vision blurring and crusting 12. It has been shown that such concentration cause notable toxicity and increased cholesterol and triglycerides levels in plasma after intraperitoneal injection in rats 13.…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous solutions of P407 above a concentrations of about 20% (w/w) are liquid when refrigerated, but gel upon warming 11. However, application of concentrated polymer solutions (>16%) in drug delivery may be disadvantageous as it changes the osmolality of the formulation, kinetics of gelation, and causes discomfort in ophthalmic applications due to vision blurring and crusting 12. It has been shown that such concentration cause notable toxicity and increased cholesterol and triglycerides levels in plasma after intraperitoneal injection in rats 13.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, for a model study, we have chosen the hydroxypropylcellulose (HPC) as a proton-accepting polymer and poly(acrylic acid) (PAA) as a proton-donating polymer to study how the complexation between these two polymers affect the LCST of the HPC polymer under various conditions. Our literature survey shows that studies of the structure and properties of interpolymer complexes between poly(acrylic acid) and nonionic cellulose ethers have been reported. Specifically, Budtova and co-workers 15-17 investigated the formation and properties of the interpolymer complexation between PAA and cellulose ethers including hydroxyethylcellulose (HEC) and methylcellulose (MC). Their experimental results showed that the mixtures of the cellulose ethers and nonionized PAA in aqueous solution formed interpolymer complexes due to hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%
“…Our literature survey shows that studies of the structure and properties of interpolymer complexes between poly(acrylic acid) and nonionic cellulose ethers have been reported. [15][16][17][18][19][20][21][22][23] Specifically, Budtova and co-workers [15][16][17] investigated the formation and properties of the interpolymer complexation between PAA and cellulose ethers including hydroxyethylcellulose (HEC) and methylcellulose (MC). Their experimental results showed that the mixtures of the cellulose ethers and nonionized PAA in aqueous solution formed interpolymer complexes due to hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%
“…The high concentrations of these polymers may cause unfavorable interactions during use under physiological conditions. While US Patent 5252318 [28] reports reversible gelling compositions which are made of physical blends of a pHsensitive gelling polymer (such as a cross-linked polyacrylic acid) and a temperature-sensitive gelling polymer (such as methyl cellulose or block copolymers of polyoxoethylne and polyoxopropylene). This patent also describes a gel system from the mixtures of polyoxyethylene and polyoxypropylene condensed with ethylenediamine.…”
Section: Thermo-responsive Pulsatile/ Triggered Releasementioning
confidence: 99%